Proposta de criação de podcast educativo piloto no âmbito do Fundo Nacional de Desenvolvimento da Educação - Araújo, Fabrício Batista de (2021)
This descriptive memorial deals with the production of podcasts in the National Fund for the Development of Education - FNDE, federal agency linked to the Ministry of Education. It is specifically about two pilot seasons, one being Educorp - Money Direct at School Program, a program financed by the Federal Government and the other Educorp - Quality of Life Program at FNDE. For the development of the aforementioned products, it was necessary to identify the problem presented by the federal agency regarding its ability to transmit information in the way that the programs within its competence, so that it could be identified how the production of podcasts within the scope of the FNDE could contribute to the achievement of organizational objectives. Therefore, we sought to produce, record and edit the pilot podcast season, according to the strategic FNDE'S planning, in addition to trying to demonstrate the possibilities of the podcast as a communication tool applied to education and to design strategies of the podcast as a communication element in corporative education. Therefore, the planning and production phase of the products passed, observing phases such as pre-production, production and post-production of podcasts, which are detailed in this memorial. It was also necessary to carry out a theoretical research on the production of podcasts for educational purposes, with their characteristics, possibilities and applications in the educational context, as well as a bibliographic review related to the podcast theme and how this media has appeared in academic research. Finally, it was concluded that the podcast media can be a relevant tool in the educational context, and that podcasts produced within the scope of FNDE can be a strong ally in achieving organizational objectives, especially in relation to information provided to the external public. referring to programs and projects financed by FNDE and as a means of communication with its internal public.